Tourism awareness ANALISIS ISI KONTEN INSTAGRAM @BATAMTOURISM_OFFICIAL PADA KESADARAN WISATA FOLLOWERS - Porang, Alfian Juanda Putra; Abidin, Sholihul (SCIENTIA JOURNAL, 2023)
@Batamtourism_Official is an account based in Batam City and managed by the Batam CityCulture and Tourism Office. This account presents tourism content that focuses on touristdestinations around the Batam area, which have a lot of tourism potential, as a space todescribe the state of tourism in the Batam City area. The purpose of this research is to findout the extent of tourism awareness among Instagram @Batamtourism_official contentfollowers. This study also uses the new media theory from Pierre Levy as a support forobserving interactions between followers and these accounts to determine the level oftourism awareness of their followers. This account often uploads various publicationsregarding tourist attractions and events organized by local governments and localcommunities. The content uploaded by this account is an important factor in increasingtourism awareness for followers. Such content is designed to convince and persuade peopleto take actions that benefit certain parties in the travel industry. With technology andinformation that is easily accessible, the need for tourist information is more fulfilled for users,and this is one of the benefits of the content provided by @Batamtourism_Official inincreasing tourism awareness for followers